Room-temperature creation and conversion of individual skyrmion bags in magnetic multilayered disks - Quan Liu; Shouzhe Dong; Yutong Wang; Junhang Liu; Guofu Xu; Hua Bai; Hao Bai; Weideng Sun; Zhiying Cheng; Yunjie Yan; Guozhi Chai; Jing Ma; et al. (Nature Communications)
Abstract Skyrmion bags, with arbitrary topological charge Q, have recently attracted much interest, since such high-Q topological systems could open a way for topological magnetism research and are promising for spintronic applications with high flexibility for information encoding. Investigation on room-temperature skyrmion bags in magnetic multilayered structures is essential for applications and remains unexplored so far. Here, we demonstrate room-temperature creation and manipulation of individual skyrmion bags in magnetic multilayered disks. Individual skyrmion bags with varying topological charges are identified to remain stable at zero field. Furthermore, we realize intriguing field-driven topological conversion of skyrmion bags, as well as local manipulation of skyrmion bags via magnetic tips. Micromagnetic simulations indicate that the special boundary condition of the disks is responsible for skyrmion-bag formation and stability. These findings provide a platform to investigate individual skyrmion bags in confined multilayered structures, which could be useful for developing high-Q-based topological spintronic devices.